The Epigenetics of Renal Cell Tumors: from Biology to Biomarkers - Henrique, Rui; Luis, Ana; Jeronimo, Carmen (Frontiers in Genetics, 2012)
Renal cell tumors (RCT) collectively constitute the third most common type of genitourinary neoplasms, only surpassed by prostate and bladder cancer. They comprise a heterogeneous group of neoplasms with distinctive clinical, morphological and genetic features. Epigenetic alterations are a hallmark of cancer cells and their role in renal tumorigenesis is starting to emerge. Aberrant DNA methylation, altered chromatin remodeling / histone onco-modifications and deregulated microRNA expression not only contribute to the emergence and progression of RCTs, but owing to their ubiquity, they also constitute a promising class of biomarkers tailored for disease detection, diagnosis, assessment of prognosis and prediction of response to therapy. Moreover, due to their dynamic and reversible properties, those alterations represent a target for epigenetic-directed therapies. In this review, the current knowledge about epigenetic mechanisms and their altered status in RCT is summarized and their envisaged use in a clinical setting is also provided.